Benefits of Implicit Regulation of Instructed Fear: Evidence From Neuroimaging and Functional Connectivity - Zhang, Yicheng; Chen, Shengdong; Deng, Zhongyan; Yang, Jiemin; Yuan, Jiajin (Frontiers in Neuroscience, 2020)
Instructed fear, which denotes fearful emotion learned by others’ verbal instructions, is an important pathway of humans’fear acquisition. Maladaptive instructed fear produces detrimental effects on health, but little is known about performing an efficient regulation of instructed fear and its underlying neural substrates. To address this question, twenty-six subjects performed an instructed fear task where emotional experiences and functional neuroimages were recorded during watching, explicit regulation (calmness imagination) and implicit regulation (calmness priming) conditions. Results showed that the implicit regulation decreased the activities of the left amygdala and the left insula for instructed fear, which was absent in explicit regulation. Moreover, the implementation of implicit regulation did not increase activities in the frontoparietal control regions, while explicit regulation increased dorsolateral prefrontal cortex activity. Furthermore, implicit regulation increased functional connectivity between the right amygdala and the right fusiform gyrus, and decreased functional connectivity between the right medial temporal gyrus and left inferior frontal gyrus, the key nodes of memory retrieval and cognitive control networks, respectively. These findings suggest a more favorable effect of implicit regulation on instructed fear, which is subserved by less involvement of control-related brain mechanisms.